2015
DOI: 10.1055/s-0035-1549958
|View full text |Cite
|
Sign up to set email alerts
|

Critical Power in Laboratory and Field Conditions Using Single-visit Maximal Effort Trials

Abstract: To compare critical power (CP) and the maximum work performed above CP (W') obtained from a single-visit laboratory test with a single-visit field test, 10 trained cyclists (V˙O(2max) 63.2±5.5 mL·min(-1)·kg(-1)) performed a laboratory and a field test. The laboratory test consisted of 3 trials to exhaustion between 2-15 min and the field test comprised 3 maximal efforts of 2, 6 and 12 min, where power output was measured using a mobile power meter. CP and W' were estimated using 3 mathematical models (hyperbol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…For example, in a young adolescent athlete with a CS of 3.17 m·s ) in the trained and untrained participants, respectively. Finally, our study revealed that the distance above critical speed (D′) is less reliable than CS, which is in agreement with previous studies [15,16,24,25]. On average, the CV ranged from 9.3% to 13.6% and the 95% CI from 7.7% to 24.6%, indicating a limited reliability and thus practical relevance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, in a young adolescent athlete with a CS of 3.17 m·s ) in the trained and untrained participants, respectively. Finally, our study revealed that the distance above critical speed (D′) is less reliable than CS, which is in agreement with previous studies [15,16,24,25]. On average, the CV ranged from 9.3% to 13.6% and the 95% CI from 7.7% to 24.6%, indicating a limited reliability and thus practical relevance.…”
Section: Discussionsupporting
confidence: 88%
“…An additional explanation for the inconsistency found in untrained athletes might be the order of the prediction trials. While some studies started with the longest trial [15,16], others started with the shortest trial or randomly applied the trials [24,25]. Starting with the shortest trial in the present study, could have affected the untrained athletes due to inexperience with maximal efforts and this in turn might impact consistency.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This difference supported the conclusion that tolerance is lower during exercise in the severe field in cycle ergometer (laboratory), influencing changes in the result of the mathematical model and, therefore, in the CP values (adjustment slope) and W '(adjustment intercept). However, Karsten et al 21 and Triska et al 22 could not confirm the existence of differences between CP values assessed in different contexts. For Karsten et al 21 , even differences observed for t Lim , final [La-] and pedal power during velodrome (3, 7 and 12 min) and laboratory (80, 100 and 105% iVȮ 2 max) were determinant to change the CP value, even analyzing it by different linear adjustments (W-t Lim and W-1/ t Lim ) in velodrome (234.0±24.4 vs. 235.0±24.1 W) and laboratory (234.0 ± 25.5 vs. 236.0 ± 29.1 W).…”
Section: Discussionmentioning
confidence: 90%
“…For Karsten et al 21 , even differences observed for t Lim , final [La-] and pedal power during velodrome (3, 7 and 12 min) and laboratory (80, 100 and 105% iVȮ 2 max) were determinant to change the CP value, even analyzing it by different linear adjustments (W-t Lim and W-1/ t Lim ) in velodrome (234.0±24.4 vs. 235.0±24.1 W) and laboratory (234.0 ± 25.5 vs. 236.0 ± 29.1 W). In the study by Triska et al 22 , the evaluation of CP in laboratory and field conditions provided similar values (280W vs. 281W, respectively); however, the authors warned against reciprocal use due to the high variability of ~7% (95% CI: -55 to 50W) in the CP evaluation between contexts. In the present study, it was observed that many of the information described for cycling apply to track and treadmill running conditions.…”
Section: Discussionmentioning
confidence: 98%